Colorimetric determination of urea using diacetyl monoxime with strong acids - Langenfeld, Noah James; Payne, Lauren Elizabeth; Bugbee, Bruce (PLOS ONE, 2021)
Urea is a byproduct of the urea cycle in metabolism and is excreted through urine and sweat. Ammonia, which is toxic at low levels, is converted to the safe storage form of urea, which represents the largest efflux of nitrogen from many organisms. Urea is an important nitrogen source in agriculture, is added to many industrial products, and is a large component in wastewater. The enzyme urease hydrolyzes urea to ammonia and bicarbonate. This reaction is microbially mediated in soils, hydroponic solutions, and wastewater recycling and is catalyzed in vivo in plants using native urease, making measurement of urea environmentally important. Both direct and indirect methods to measure urea exist. This protocol uses diacetyl monoxime to directly determine the concentration of urea in solution. The protocol provides repeatable results and stable reagents with good color stability and simple measurement techniques for use in any lab with a spectrophotometer. The reaction between diacetyl monoxime and urea in the presence of sulfuric acid, phosphoric acid, thiosemicarbazide, and ferric chloride produces a chromophore with a peak absorbance at 520 nm and a linear relationship between concentration and absorbance from 0.4 to 5.0 mM urea in this protocol. The lack of detectable interferences makes this protocol suitable for the determination of millimolar levels of urea in wastewater streams and hydroponic solutions.